Slow associative learning in alcohol dependence and the alcohol cue exposure treatment paradox. - Buckfield, Carl; Sinclair, Julia M. A.; Glautier, Julia (Addiction, 2021)
Aims: To examine two explanations for the observation that cue–exposure treatment has not been clearly effective in the treatment of alcohol dependence: do alcohol‐dependent individuals have either (1) slower extinction and/or (2) greater contextual specificity of extinction than non‐dependent individuals? Design In two exploratory laboratory experiments we used mixed factorial designs with two‐group between‐subjects factors and within‐subjects factors corresponding to performance in different parts of a computer‐based learning task. Setting: University of Southampton psychology research laboratories and two addiction treatment services in the city of Southampton, UK. Participants: Experiment 1: 74 (54 female) undergraduates from the University of Southampton (age mean = 20.4 years). Experiment 2: 102 (40 female) participants from the University of Southampton, the local community, and from two Southampton alcohol treatment services (age mean = 41.3 years). Measurements: The Alcohol Use Disorders Identification Test, a 1‐week time‐line follow‐back alcohol consumption questionnaire, the Barratt Impulsiveness Scale (11th edn), and a computerized learning task. Experiment 2 additionally used the 44‐item Big Five Inventory, a drug use history checklist, and the Hospital Anxiety and Depression Scale. Findings Experiment 1: light and heavy drinkers did not differ significantly in extinction [extinction block × drinking status interaction, P = 0.761, ηp2=0.005, 95% confidence interval (CI) = (0,0.028)] or on contextual control of extinction [recovery block × drinking status interaction, P = 0.514, ηp2=0.009, 95% CI =(0, 0.084)]. Experiment 2: slower extinction in abstinent alcohol‐dependent participants compared with light drinkers [extinction block × drinking status interaction, P = 0.023, ηp2=0.031, 95% CI = 0, 0.069)] but no significant difference on contextual control of extinction [recovery block × drinking status interaction, P = 0.069, ηp2=0.033, 95% CI = (0, 0.125)]. Conclusion: Abstinent alcohol‐dependent people may have slower extinction learning for alcohol‐related cues than non‐dependent light drinkers.